The past and future of tuberculosis research. - Iñaki Comas; Sebastien Gagneux (PLoS Pathogens)
Renewed efforts in tuberculosis (TB) research have led to important new insights into the biology and epidemiology of this devastating disease. Yet, in the face of the modern epidemics of HIV/AIDS, diabetes, and multidrug resistance--all of which contribute to susceptibility to TB--global control of the disease will remain a formidable challenge for years to come. New high-throughput genomics technologies are already contributing to studies of TB's epidemiology, comparative genomics, evolution, and host-pathogen interaction. We argue here, however, that new multidisciplinary approaches--especially the integration of epidemiology with systems biology in what we call "systems epidemiology"--will be required to eliminate TB.